Algorithm for constructing routing to ensure fault tolerance of the communication network - G. O. Sorokin; A. V. Sinitsyn (Informaciâ i Innovacii)
Introduction. The efficiency, reliability and scalability of a  communication network largely depend on the choices made by the routing algorithm. This is especially true now, due to frequent escalations of military conflicts, the consequences of which can affect the stability and reliability of network communications.Purpose. Formalization of an algorithm that ensures fault tolerance of a communication network by constructing optimal routing.Methods. Mathematical modeling, as well as experimental testing of the presented model based on various geodata through the practical implementation of a formalized algorithm.Results. A mathematical model of the algorithm is proposed, which is based on algorithms for constructing a minimum spanning tree, as well as an example of its implementation.Conclusions. The presented algorithm allows you to build routing that ensures fault tolerance of the communication network, in conditions of theoretical destruction of nodes in communication networks by determining the probability of the existence of adjacent nodes.